PEMASARAN SYARIAH BERBANTUAN MEDIA SOSIAL: KONTESTASI STRATEGIS PENINGKATAN DAYA JUAL (IAIN Tulungagung, 2019)
The emergence of instant products has a major impact on people's perspectives and behavior. Many people do not want to be difficult in owning a house, so PT Karya Cipta Sakinah uses this great opportunity to build a medium-sized business that is engaged in the developer. The business that was carried out began with the use of own capital which is now expanding into a larger business aimed at supporting the government's